2014
DOI: 10.1590/0100-2945-271/13
|View full text |Cite
|
Sign up to set email alerts
|

Formas de esterilização do GA3 e reação morfogênica em microestacas de mamoeiro

Abstract: RESUMO -Este trabalho objetivou estudar os efeitos do ácido giberélico (GA 3 ) sobre o alongamento de brotos de mamoeiro 'Tainung 01' em meio de multiplicação in vitro e posterior enraizamento ex vitro. Brotações com menos de 1 cm de comprimento foram submetidas ao alongamento em meio MS contendo GA 3 , nos seguintes tratamentos, em mg L -1 : T 1 = 0,0; T 2 = 0,5 esterilizado junto com o meio de cultura; T 3 = 0,5 esterilizado a frio; T 4 = 2,0 esterilizado junto com o meio de cultura; T 5 = 2,0 esterilizado a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the present study, the plants treated with GA showed a less vigorous aspect, with reduced height during this season; however, there were no phytotoxicity effects such as etiolation, yellowing, chlorosis or necrosis. The phytotoxicity of GA was observed by Oliveira et al (2014) in micro-cuttings of 'Tainung 01' papaya under the treatment consisting of the highest dose used (2.0 mg L -1 ), which caused damage to leaf development, with symptoms of yellowing.…”
Section: Figurementioning
confidence: 99%
“…In the present study, the plants treated with GA showed a less vigorous aspect, with reduced height during this season; however, there were no phytotoxicity effects such as etiolation, yellowing, chlorosis or necrosis. The phytotoxicity of GA was observed by Oliveira et al (2014) in micro-cuttings of 'Tainung 01' papaya under the treatment consisting of the highest dose used (2.0 mg L -1 ), which caused damage to leaf development, with symptoms of yellowing.…”
Section: Figurementioning
confidence: 99%